Influences on the development of a strategy for a local community based mental health service: a medical perspective - Buchan, Terry (Curtin University, 2003)
The history of the care of the mentally ill in Britain, which has been broadly reflected in Western Australia since 1826, can be conveniently, if simplistically divided into a number of epochs. Each epoch is characterised by a particular focus or paradigm of clinical management, which prevails over a period of time but is then followed by a comparatively short period of rapid change to a new paradigm. Such changes are shaped by a number of forces, but three categories can be readily identified. These are: concepts of mental illness; reactions of administrative systems and the attitudes of medical practitioners. As the concept of the nature of mental illness has changed, succeeding epochs have evolved to a more humane and enlightened approach to the mentally ill. Nevertheless, each management paradigm has failed to deliver the expected 'cures' and the consequent reduction in the burden of illness. Each has been replaced by a new and radically different paradigm, often at enormous cost, but there has been no progressive evolution towards a system that incorporates measures that have proven value. In recent years 'Community Care', has failed in such a manner that there have been strong arguments that it should be abandoned. At the same time there is evidence that a new paradigm 'Primary Care Psychiatry' is emerging as government policy. The challenge is to preserve the best elements of community care and integrate Primary Care Psychiatry into the broader framework. The best chance of achieving this is to develop a gradual, evolutionary process, built on consensus between psychiatrists, general practitioners and administrators.The purposes of the present research are threefold: to develop a conceptual model for an optimal community based mental health service. Then by examining the views of general practitioners, psychiatrists and administrators, determine the degree of congruence of these views. This is achieved by a qualitative study comprising extended interviews with 24 GPs, 15 psychiatrists and 11 administrators. This approach is chosen over a more broadly based, structured questionnaire approach for two reasons. Firstly, the views expressed in informal face to face interviews are more likely to be true expressions of opinion, especially when these are critical. Secondly, by using a comparatively unstructured approach, the stakeholders are able to express views on issues that they consider important. Finally, the areas of consensus and disagreement are analysed and recommendations made on strategies to develop a plan for a practical, viable service in a local area.